Notes on the flora of the Yucatan Peninsula IV: Marsilea vestita Hook. Et grev. var. vestita (Marsileaceae), a new record and some comments about the genus in the region - Duno de Stefano, R.=700 1 Carnevali Fernandez Concha, G.
(Es, En)